Intramyocellular lipid variations in active older men: relationship with aerobic fitness. (27th December 2012) - Rouffet, D.; Villars, C.; Fissoune, R.; Sappey‐Marinier, D.; Laville, M.; Ibarrola, D.; Sothier, M.; Monnet, M.‐F.; Ovize, M.; Bonnefoy, M.; Boesch, C.; Canet‐Soulas, E.
Abstract Aims Intramyocellular lipid (IMCL) variations in older men are poorly explored. In young adults, IMCL can be influenced by both diet and exercise interventions; this flexibility is related to aerobic fitness. We evaluated in active older adults the influence of maximal aerobic capacity on short‐term diet and exercise‐induced variations in IMCL stores. Methods Intramyocellular lipids were measured by 1H magnetic resonance spectroscopy (1H‐MRS) after a 3‐day fat depletion‐replenishment diet (IMCLFDR) and immediately after a 2‐h exercise at 50% VO2 max (IMCLFDR_EX). To further explore diet influence, the protocol was repeated after a high‐fat diet (HF), with both pre‐ and post‐exercise measurements (IMCLHF and IMCLHF_EX). Results In active older men (69.8 ± 5.2 years), IMCLFDR was lowered by exercise (IMCLFDR = 3.45 ± 1.52 vs. IMCLFDR_EX = 2.74 ± 1.15 mmol kg−1 wet weight, P < 0.05), and exercise‐induced variations were correlated to the initial store (P < 0.05, r = −0.72). IMCLFDR was linked with aerobic fitness (P < 0.05, r = 0.76), when adjusted by fat mass. IMCLHF was lower than IMCLFDR (P < 0.05), decreased after exercise (P < 0.05) and varied also as a function of initial store (P < 0.05, r = −0.89), but without link with aerobic fitness. Finally, diet‐induced IMCL store variations were positively linked to aerobic fitness (P < 0.05, r = 0.89). Conclusion Variations of the IMCL stores in physically active older adults appear related to aerobic fitness, with similarly fast adaptation to short‐term interventions combining diet and exercise as young active adults.